1988
DOI: 10.1002/syn.890020511
|View full text |Cite
|
Sign up to set email alerts
|

Organization of dopamine D1 and D2 receptors in human striatum: Receptor autoradiographic studies in Huntington's disease and schizophrenia

Abstract: The technique of quantitative autoradiography was used to examine the effects of Huntington's disease (HD) and schizophrenia on the organization of striatal dopamine (DA) D1 and D2 receptors. Whereas the striatum of HD cases showed a reduction in the density of D1 ([3H]SCH 23390) and D2 ([3H]spiroperidol) receptors, the patterning of D2 receptor loss did not match that of the D1 receptor loss. The HD loss of D1 D1 receptors (65%) is far greater than the loss of D2 receptors (28%). Whereas there was a dorsal-ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(79 citation statements)
references
References 45 publications
5
74
0
Order By: Relevance
“…This is consistent with previous studies that show two to threefold higher densities in the isocortex than in the basal ganglia and hippocampus (Pazos et al 1987b;Schotte et al 1983). We did not fInd a heterogeneous pattern of 5-HTIA or 5-HT2 receptors in the striatum, unlike that for DA receptors (Joyce et al 1986(Joyce et al , 1988(Joyce et al , 1991, muscarinic receptors (Lowenstein et al 1990), and 13-adrenergic receptors (Joyce et al 1992) .…”
Section: Striatummentioning
confidence: 63%
See 1 more Smart Citation
“…This is consistent with previous studies that show two to threefold higher densities in the isocortex than in the basal ganglia and hippocampus (Pazos et al 1987b;Schotte et al 1983). We did not fInd a heterogeneous pattern of 5-HTIA or 5-HT2 receptors in the striatum, unlike that for DA receptors (Joyce et al 1986(Joyce et al , 1988(Joyce et al , 1991, muscarinic receptors (Lowenstein et al 1990), and 13-adrenergic receptors (Joyce et al 1992) .…”
Section: Striatummentioning
confidence: 63%
“…Receptor autoradiography can be a particularly use ful tool for exploring the altered expression of trans mitter systems in brains of patients with neuropsy chiatric disorders (Joyce et al 1988(Joyce et al , 1992. Studies that directly explore the relationship between the distribu tion of 5-HT uptake sites and 5-HT receptors in human brain by using autoradiographic means have not been published.…”
mentioning
confidence: 99%
“…Numerous amyloid deposits have been identified in the striatum in AD, particularly in those with parkinsonian features, and this may contribute to altered processing of proteins in these cells (e.g., receptors) (Braak and Braak 1990). Consequently, the ability of striatal neurons to synthesize D 2 receptor protein and transport these proteins to the appropriate synapses may be significantly affected (see Joyce et al 1988). However, it is unclear why D 2 -like receptors would be reduced in number when other DA (e.g., D 1 ) receptors expressed in the striatum were not.…”
Section: Discussionmentioning
confidence: 99%
“…For autoradiographic experiments, the brains were sectioned at 20 m in a Lipshaw 1800-N cryotome at Ϫ 15 Њ C, thaw-mounted onto gelatin subbed slides, dried at 0 Њ C under reduced pressure, and then stored at Ϫ 70 Њ C until further use. (Joyce et al 1988). Slide-mounted sections were brought to 0 Њ C 30 min prior to incubation.…”
Section: Human Tissue Acquisition and Preparationmentioning
confidence: 99%
“…For instance, schizophrenic patients may have greater dopaminergic innervation in the striatum. Regulation of transmitter release, and uptake, could be normal, while greater terminal density could lead to more release of dopamine after re-uptake blockade and vesicular release by amphetamine.Although post-mortem studies have found normal density of presynaptic dopamine markers, such as the dopamine transporter (Hirai et al 1988;Joyce et al 1988;Pearce et al 1990) and expressed mRNA for tyrosine hydroxylase (Ichinose et al 1994), excessive innervation could be obscured by normal aging and more rapid degeneration of terminals in schizophrenia. Dopamine receptors Volkow et al 1996b), transporters (Volkow et al 1996a), and vesicles (Frey et al 1998 all decline with aging, with rates estimated at 2-8% per decade.…”
mentioning
confidence: 99%